Tuning in and hanging out: A preliminary study of college students’ use of podcasts for information, entertainment, and socializing - Swanson, Douglas J. (Social Science Journal, 2012)
Abstract: Millions of listeners tune in to Internet-based audio-on-demand programming (commonly known as audio podcasts). College students represent a large and influential group of consumers but little is known about this primary audience''s podcast listening choices and related opinions. This research was organized within the uses and gratifications perspective and involved an online survey of college students who identified as podcast listeners. Results showed most collegiate listeners spent no more than an hour a month listening to podcasts, and fewer than half reported listening to all the episodes they downloaded. Most listeners found podcasts fun and entertaining and said they enjoy sharing what they have heard with peers. Respondents reported clearly identified program genre preferences, and reported ‘multitasking’ in a variety of specific ways while listening. This research does not attempt to answer all questions about the college student podcast audience, but it is a starting point for further study into this important user group. Recommendations for future research are offered.